MALAYSIAN-OMANI HISTORICAL AND CULTURAL RELATIONSHIP: IN CONTEXT OF HALWA MASKAT AND BAJU MASKAT - Rahmah Ahmad H. Osman; Md. Salleh Yaapar; Elmira Akhmatove; Fauziah Fathil; Mohamad Firdaus Mansor Majdin; Nabil Nadri; Saleh Alzeheimi (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The current re-emergence of global maritime activity has sparked initiative from various nations in re-examining their socio-political and cultural position of the region. Often this self-reflection would involve the digging of the deeper origin and preceding past of a nation from historical references and various cultural heritage materials. From this, realisation of the pattern in maintaining an empire or enterprise from the immediate ancestral society could be turned into a model or benchmark in developing the present and future planning of the nation. In the context of Islamic civilisation development along the Indo-Pacific seaboard the Omani and Malay nations are the two integral entities that had assumed their central role as seafarers, traders, rulers, and travellers in maintaining the dynamics of the region and this happened as early as the Islamic period of the 9th and 10th century CE up till 16th and 19th century when series of European colonial infiltration disrupted greatly the balance of this classical network. The Kitab at-Tarikh Silsilah Negeri Kedah, for instance, presented a vivid story of an Omani captain and his ship in the early 1700s who had met Kedahan people. The cultural heritage of the Arabian Gulf brought mainly by the Omanis could even be found there such as a fabric product known as Baju Maskat and a kind of delicacy known as Halwa Maskat which signal that the cultural hegemony of the Omanis indeed exceeded their immediate political boundary.